Reflective Practice for Patient Benefit: An Analysis of Doctors' Appraisal Portfolios in Scotland. Issue 1 (2019) - Wakeling, Judy; Holmes, Sarah; Boyd, Alan; Tredinnick-Rowe, John; Cameron, Niall; Marshall, Martin; Bryce, Marie; Archer, Julian
Abstract : Introduction: Reflective practice has become the cornerstone of continuing professional development for doctors, with the expectation that it helps to develop and sustain the workforce for patient benefit. Annual appraisal is mandatory for all practicing doctors in the United Kingdom as part of medical revalidation. Doctors submit a portfolio of supporting information forming the basis of their appraisal discussion where reflection on the information is mandated and evaluated by a colleague, acting as an appraiser. Methods: Using an in-depth case study approach, 18 online portfolios in Scotland were examined with a template developed to record the types of supporting information submitted and how far these showed reflection and/or changes to practice. Data from semistructured interviews with the doctors (n = 17) and their appraisers (n = 9) were used to contextualize and broaden our understanding of the portfolios. Results: Portfolios generally showed little written reflection, and most doctors were unenthusiastic about documenting reflective practice. Appraisals provided a forum for verbal reflection, which was often detailed in the appraisal summary. Portfolio examples showed that reflecting on continued professional development, audits, significant events, and colleague multisource feedback were sometimes considered to be useful. Reflecting on patient feedback was seen as less valuable because feedback tended to be uncritical. Discussion: The written reflection element of educational portfolios needs to be carefully considered because it is clear that many doctors do not find it a helpful exercise. Instead, using the portfolio to record topics covered by a reflective discussion with a facilitator would not only prove more amenable to many doctors but would also allay fears of documentary evidence being used in litigation.